Poéticas do queer: uma investigação da escrita de João Gilberto Noll e Glauco Mattoso - Silva, Joao Pedro Cerdeira Lelis [UNIFESP] (2020)
This dissertation proposes to discuss the concept of “queer poetics”, through the reading of the novels Acenos e afagos (2008) and Manual do Podolatra Amador (2006), by the novelist and short story writer João Gilberto Noll and the novelist and poet Glauco Mattoso, respectively - two authors whose literary works are marked by a centrality of homoeroticism, as well as a displacement of the normative discourses that would regulate and mediate in a normative way the body and sex –, in order to establish comparisons regarding common structures and elements that could outline a queer poetics. Based on the definition of Tamsin Spargo (2018) and Anselmo Peres Alós (2010), that what fundamentally characterizes queer is its opposition to the notions of normality in the field of sex and gender based on their historical and discursive constructions, we intend to take into account the gay and queer aspects in their texts not as a prescriptive representation, but, as proposed by Denilson Lopes (2002), as a series of elements inside the structure of the literary text, since, as suggested by the American philosopher Judith Butler in the introduction of her Gender Trouble (2003), representation would act as a normative force in language, creating and regulating what it should merely represent. Therefore, we find in comparative literature the tools that make it possible to think about a poetics in a descriptive way, avoiding a prescriptive character that would, by definition, be contrary to queer. Finally, this research aims to reflect and contribute to the academic debate regarding the intersections between queer studies, gay and lesbian studies and literary studies, with a theoretical discussion that, anchored in the comparative study of these Brazilian authors, intends to reflect theoretically on the characteristics and limits of what could be called "queer writing", concatenating elements and discussions about language, authorship, alterity, subjectivity and performance.